Ankle-Brachial Index predicts Coronary Artery Disease associated with Peripheral Arterial Disease - Habib, SM Ahsan; Islam, M Nazrul; Pasha, Kamal; Alam, Saleh Ahmed Nurul; Mohsin, Khaled; Islam, Khandakar Kamrul; Ullah, Muhammad; Khalequzzaman, Md; Siddique, Md Abu (University Heart Journal, 2011)
Most common cause of Peripheral Arterial Disease (PAD) is atherosclerosis. Atherosclerosis is a generalized disease, also involving coronary and carotid arteries. Often atherosclerotic coronary artery disease (CAD) is associated with PAD. This prospective observational study was conducted in the National Institute of Cardiovascular Diseases, Dhaka, Bangladesh, during July 2004 to June 2005. Total 58 patients with PAD were included in the study. Patients were classified as group I having normal coronary artery, group II insignificant CAD (Left main <50% stenosis, others <70% stenosis) and group III, significant CAD (Left main ≥50% stenosis, others ≥70% stenosis). Ankle-brachial index was significantly low (0.75±0.25 Vs 0.37±0.40) in the patients with coronary artery disease (Group II and III) compare to non-CAD (P =0.001).This study suggests that ankle-brachial index (ABI) have significant relation with the presence of CAD. Key words: Ankle-Brachial Index; peripheral arterial disease DOI: 10.3329/uhj.v6i1.7186 University Heart Journal Vol.6(1) 2010 pp.23-25